Peran Konsep Matematika dalam Berbagai Aspek Kehidupan - Yoga, M. Rafi Prima (Maliki Interdisciplinary Journal, 2025)
This study discusses the role of mathematical concepts in various aspects of community life, including economics, agriculture, education, social affairs, government, and culture. The analysis was conducted through a literature review by examining scientific works, journals, and trusted references. The findings show that mathematics is not only a tool for calculation but also a means to develop critical thinking skills, support decision-making, and foster character building. In the economic field, mathematics serves as a regulator of economic activities. In agriculture, it is used to determine patterns. In education, the application of technologies such as GeoGebra and contextual learning has proven to enhance mathematical connections and student creativity. In social activities, mathematics plays an important role in maintaining order and harmony in social interactions. In state governance, mathematics supports public policy planning through economic modeling, statistics, and electoral methods such as the Sainte-Laguë system. In the cultural sphere, mathematics is reflected in batik patterns, temple architecture, and carvings that employ Fibonacci patterns and geometric concepts. These findings affirm that mathematics serves as a crucial foundation for societal progress, not only in practical aspects but also as a medium for preserving cultural values and developing essential life skills.